2009
DOI: 10.1111/j.1526-4610.2009.01399.x
|View full text |Cite
|
Sign up to set email alerts
|

An Internet‐Based Migraine Headache Diary: Issues in Internet‐Based Research

Abstract: The Internet-based headache diary is a feasible, acceptable data collection tool that can access geographically diverse populations who have not previously participated in research studies. Use of an Internet-based approach was found to be feasible for recruitment and retention of such diverse populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 43 publications
2
31
0
Order By: Relevance
“…More recently, other authors explored, in migraine patients, the feasibility and acceptability of an internet-based headache diary, compared with their standard paper diary [10]. This study showed that the internet-based headache diary was not only a feasible and acceptable data collection tool, but also an accessible option for different populations.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, other authors explored, in migraine patients, the feasibility and acceptability of an internet-based headache diary, compared with their standard paper diary [10]. This study showed that the internet-based headache diary was not only a feasible and acceptable data collection tool, but also an accessible option for different populations.…”
Section: Introductionmentioning
confidence: 99%
“…One approach to address this challenge is to provide migraine patients with a headache diary to complete in-between visits (McKendrick and Badcock, 2004b;Nguyen et al, 2014). The diary or series of questions could be incorporated online (Moloney et al, 2009) or into an application that is accessible via portable devices (Turpin et al, 2014) to enable date-and time-stamping and more 'real-time' tracking of changes in an individual's migraine history over time. Given inter-individual variability in migraine features, as well as known fluctuations in the results of clinical tests of vision in migraine sufferers, it is not always useful to simply look for group differences.…”
Section: Do Migraine Medications Affect Clinical Test Results?mentioning
confidence: 99%
“…These studies have been limited in their sample selection (e.g., Barrett and Barrett, 2001; Helzer et al, 2006; Kaminer et al, 2006; Kranzler et al, 2004; Lee, Choi, and Beal, 2006; Toll et al, 2006; Vivoda and Eby, 2006), variety of method use (e.g., Armeli et al, 2008; Baer, Saroiu, and Koutsky, 2002; Herbenick et al, 2011; Kiene et al, 2009; Moloney et al, 2009; Park, Armeli, and Tennen, 2004), topical focus (e.g., Armeli et al, 2008; Baer, Saroiu, and Koutsky, 2002; Herbenick et al, 2011; Kiene et al, 2009; Moloney et al, 2009; Park, Armeli, and Tennen, 2004), and time span of data collection (e.g., Aldridge-Gerry et al, 2011; Merz and Roesch, 2011). Although these studies have made important contributions to the usage of new technologies in data collection, few, if any, studies have attempted frequent measurement using self-administered methods on a probability-based sample.…”
Section: 1 Journal Keepingmentioning
confidence: 99%